Synthesis of 3, 5-dichloro-4, 4-difluoro-4-bora-3a, 4a-diaza-s-indacenes (BODIPYs) via Cu(OTf)2 mediated oxidative nucleophilic substitution of hydrogen by chloride. Issue 17 (24th April 2020) - Frank, Felicity; Alice, Laura Manzoli; Mauker, Philipp; Alsimaree, Abdulrahman A.; Waddell, Paul Gordon; Probert, Michael Richard; Penfold, Thomas James; Knight, Julian Gary; Hall, Michael John
Abstract: Regioselective halogenation is often a key step in the formation of substituted 4, 4-difluoro-4-bora-3a, 4a-diaza- s -indacene (BODIPY) fluorophores, through the enablement of subsequent downstream C–C or C-X bond forming steps via SN Ar or metal catalyzed cross-coupling reactions. Classical SE Ar halogenation of unsubstituted BODIPYs results in 2/6-substitution, precluding easy access to 3/5-halogenated BODIPYs. Herein we present our development of a 3, 5-dihalogenation reaction of unsubstituted BODIPYs, via a double oxidative nucleophilic substitution of hydrogen with chloride. Reaction of a range of meso -aryl, but otherwise unsubstituted, BODIPYs with stoichiometric Cu(OTf)2 in the presence of ethanolamine and tetrabutylammonium chloride gives high isolated yields of the corresponding 3, 5-dichlorinated BODIPYs, facilitating access to these valuable synthetic intermediates. Graphical abstract: Image 1 Highlights: Regioselective 3, 5-dichlorination of unsubstituted BODIPYs is achieved. Double oxidative nucleophilic substitution of hydrogen with chloride. High yields are obtained for a range of 3, 5-dichloro meso-aryl BODIPYs.